Pengaruh Ortofosfat dan Klorinasi Terhadap Korosi dan Mikroorganisme pada Cooling Water System di Unit Utilitas-2 PT. Pupuk Iskandar Muda - Herri Supriadi; Muhammad Zaki; Syaubari . (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2017)
ABSTRACTCorrotion inhibitors and the growth of microorganisms that occur in the cooling water system can affect water quality, which causes an effect on the process temperature and temperature of the equipment. This study aims to study the effect of orthophosphate and chlorination on corrosion and microorganisms on cooling water systems, using materials such as 85% water basin cooling tower, orthophosphate [H3PO4] as 60% corrotion inhibitor, calcium hypochlorite [Ca (OCl)] as a disinfectant dissolved into water so that it becomes hypochlorite acid (HOCl). The fixed variable used is operating time every 3 hours, atmospheric cooling tower pressure, pump pressure 15 kg/cm2, feed temperature 300C, reverse temperature 400C, and 25 liter basin volume. The independent variables were orthophosphate (H3PO4) concentration of 85%: 12, 15, 18, 21, and 24 ppm, then the concentration of calcium hypochlorite [Ca(OCl)2] 60%: 53, 57, 61, 65, and 69 ppm. The results showed that the lowest corrosion value of orthophosphate corrosion inhibitor was 0.0199 grams, the highest value of microorganisms was 1000, the lowest pH value was 3.39 and the lowest residual chlorine value was 0.09 ppm while the highest use of calcium hypochlorite was 0 12 grams, the highest value of microorganisms is 0, the lowest pH value is 3.39 and the highest residual value of chlorine is 0.86 ppm in the cooling water system.